A CRITICAL DISCOURSE ANALYSIS OF GENDER DEPICTION IN EFL TEXTBOOKS AS A TEACHING MATERIAL FOR HIGHSCHOOL - Novandy Adhitya; Malia, Emma; Rivaldy, Gerry Frizky (English Education Department of STKIP Pasundan, 2022)
The increase orientation towards Gender Equality in Language Education, especially the English Language Education, calls for research to find out teachers' perceptions and their media of teaching. Textbook plays an important role as a media used in English Language Teaching. There have been numerous researches of textbooks. However, less attention has been paid to the Gender Depiction within the textbooks. Biased Gender Depiction can contribute to discriminatory practices in English Language Education. This current study concerns with topic of Gender in EFL Classroom, especially in Indonesian Context. In order to find out a more informed view on gender depiction within these materials, it was seen to be crucial to combine the theoretical outcomes of CDA and SFL with English language teachers' potential interpretation of gender depiction within textbooks. Selected textual corpus were, first, analysed using the Fairclough's Three Stages of Theoretical Framework. The three stages were description, interpretation, and explanation. The description stage was analysed using Halliday's Transitivity System of Systemic Functional Linguistics. Second, participants of four were selected to be interviewed. A Likert-type questionnaire was given prior before the interviews were conducted. The comparative analysis of the results shows that while the majority of the clauses, known as types of processes, indicating the continuation of Gender Stereotyping, most teachers see gender in the lens of egalitarian view meaning that all people regardless of their gender are equal and deserve equal rights and opportunities.